2020
DOI: 10.15446/cuad.econ.v39n80.84163
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Goodwin: Financialization as a structural change to explain the new Argentinian crisis

Abstract: This paper aims to explain the causes of the 2018/2019 Argentinian crisis by means of a growth cycle model a la Goodwin, where the aggregate demand is wage-led, the wage-share is predatory of the external sector, and the financial norm stands as an exogenous apex-predator of both real wages and the current account. Its main results allow us to understand the stylized facts of the Argentinian economy: a higher financial norm increases inequality and required current account surpluses, reduces stability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Entrepreneurship is defined by various scholars who expressed the challenge of lack of theoretical aspect, discipline and an ambiguous unit. Entrepreneurship has been defined in various disciplines which has causes lack of consensus for a single definition (Chena et al, 2020;Combita Mora, 2020;Antelm-Lanzat et al, 2020;Caliskan & Zhu, 2020;Chipeta et al, 2020;De Klerk, 2020). Initially, entrepreneurship was defined and elaborated according to five categories including psychological trait, success strategies, and formation of new ventures and effect of environmental factors (Nayyar, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Entrepreneurship is defined by various scholars who expressed the challenge of lack of theoretical aspect, discipline and an ambiguous unit. Entrepreneurship has been defined in various disciplines which has causes lack of consensus for a single definition (Chena et al, 2020;Combita Mora, 2020;Antelm-Lanzat et al, 2020;Caliskan & Zhu, 2020;Chipeta et al, 2020;De Klerk, 2020). Initially, entrepreneurship was defined and elaborated according to five categories including psychological trait, success strategies, and formation of new ventures and effect of environmental factors (Nayyar, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, preserving environmental habitats is crucial for economic development and human survival. The seminal work by Werner (1787), who laid the foundation of early geology, discussed the Earth's origin (Chena et al, 2020;Cómbita Mora, 2020;Espinosa-Espinosa et al, 2020;Sorokhtin et al, 2011). Basic research concerning the Earth revealed that, during a certain period, it was inhabitable due to high temperatures.…”
Section: Introductionmentioning
confidence: 99%